Altered Regional Brain Cortical Thickness in Pediatric Obstructive Sleep Apnea - Macey, Paul M.; Kheirandish-Gozal, Leila; Prasad, Janani P.; Ma, Richard A.; Kumar, Rajesh; Philby, Mona F.; Gozal, David (Frontiers in Neurology, 2018)
Rationale: Obstructive sleep apnea (OSA) affects 2-5% of all children, and is associated with cognitive and behavioral deficits, resulting in poor school performance. These psychological deficits may arise from brain injury, as seen in preliminary findings of lower gray matter volume among pediatric OSA patients. However, the psychological deficits in OSA are closely related to functions in the cortex, and such brain areas have not been specifically assessed. The objective was to determine whether cortical thickness, a marker of possible brain injury, is altered in children with OSA. Methods: We examined regional brain cortical thicknesses using high-resolution T1-weighted magnetic resonance images in 16 pediatric OSA patients (8 male; mean age ± SD = 8.4 ± 1.2 years; mean apnea/hypopnea index ± SD = 11 ± 6 events/hour) and 138 controls (8.3 ± 1.1 years; 62 male; 138 subjects from the NIH Pediatric MRI database) to identify cortical thickness differences in pediatric OSA subjects. Results: Cortical thinning occurred in multiple regions including the superior frontal, ventral medial prefrontal, and superior parietal cortices. The left side showed greater thinning in the superior frontal cortex. Cortical thickening was observed in bilateral precentral gyrus, mid-to-posterior insular cortices, and left central gyrus, as well as right anterior insula cortex. Conclusions: Changes in cortical thickness are present in children with OSA, and likely indicate disruption to neural developmental processes, including maturational patterns of cortical volume increases and synaptic pruning. Regions with thicker cortices may reflect inflammation or astrocyte activation. Both the thinning and thickening associated with OSA in children may contribute to the cognitive and behavioral dysfunction frequently found in the condition.